Sistem Informasi Pelanggaran Masyarakat - Mira Susanti (Riset Sinergi Indonesia (RISINDO), 2022)
Along with the times and technology that is growing longer, there have been a lot of information systems or applications that are used to help smooth a job, especially in the field of police. In order to support the performance of the police, it is necessary to provide information to the public about cases or criminal acts that occurred. Processing of violations of this law is an application to help the police provide information where this information will be received by the family of the perpetrator of the violation in the form of information on cases of violations that occurred committed by the police. his family members. The results of the trial of the information sent were received more quickly by the perpetrator's family, so that the family quickly took steps to help family members who were caught in legal cases.